OPEC's oil exporting strategy and macroeconomic (in)stability - Conraria, Luís Aguiar (2012)
Aguiar-Conraria and Wen (2008) argued that dependence on foreign oil raises the likelihood of equilibrium indeterminacy (economic instability) for oil importing countries. We argue that this relation is more subtle. The endogenous choices of prices and quantities by a cartel of oil exporters, such as the OPEC, can affect the directions of the changes in the likelihood of equilibrium indeterminacy. We show that fluctuations driven by self-fulfilling expectations under oil shocks are easier to occur if the cartel sets the price of oil, but the result is reversed if the cartel sets the quantity of production. These results offer a potentially interesting explanation for the decline in economic volatility (i.e., the Great Moderation) in oil importing countries since the mid- 1980s when the OPEC cartel changed its market strategies from setting prices to setting quantities, despite the fact that oil prices are far more volatile today than they were 30 years ago.